Mohamed in gora - Komel, Svit (Časopis za kritiko znanosti, 2018)
In the Manifesto of New Realism, Maurizio Ferraris attempts to articulate a new, "realistic" approach to the philosophy of knowledge. His main goal is to present an alternative to postmodernism, which provided a basis for the development of the post-truth society. The article starts off by introducing the authors that Ferraris identifies as constructionists and continues by analyzing the concepts he employs to engage them. The author demonstrates why Ferraris' realism fails to provide an adequate substitute for postmodernism, and attempts to answer the challenge of New Realism through a parallel reading of Gotthold Lessing, Thomas Kuhn and Hans Kelsen. By using their interpretations of different criteria for asserting the validity of propositions pertaining to the fields of religion, natural science and law, the article sets out to elevate the problem of attaining true knowledge beyond the epistemological-ontological divide. In order to reach this goal, the author compares different disciplines of knowledge, particularly law and natural science, to delineate their common epistemological premises and consequently attain a new perspective on the phenomenon of knowledge in general.
Keywords: effectiveness; epistemologija; epistemology; filozofija; knowledge; philosophy; postmodernism; postmodernizem; realism; realizem; spoznanje; spoznavna teorija; theory of knowledge; učinkovitost; validity; vednost; veljavnost; znanje